A Brief History of Interdisciplinary Cooperation in the Study of Small Groups. (April 2016) - Kettner-Polley, Richard
This article attempts to answer three questions. First, why has it been so difficult to achieve true interdisciplinary collaboration in the study of small groups? Second, what has been accomplished (and, in some cases, lost) in past attempts? And finally, what has been accomplished recently?